Bill saving analysis of rooftop PV customers and policy implications for Thailand - Chaianong, Aksornchan; Tongsopit, Sopitsuda; Bangviwat, Athikom; Menke, Christoph (Renewable Energy, 2019)
Since a new policy supporting rooftop photovoltaics (PV) will be launched in Thailand, this study investigates the economics of utility customers’ investments in rooftop PV (values of bill savings) for four customer groups (residential scale, small general service, medium general service and large general service) across electricity tariffs, PV-to-load ratios and compensation schemes (net metering and net billing). The values of the bill savings of all groups are higher under the conditions of higher buyback rates/credit, lower PV-to-load ratios, and higher retail rates. Under the current retail rate design, the values of the bill savings of residential and small general service groups are slightly higher than those of medium and large general service groups, since there are demand charges for the latter two groups that cannot be completely avoided using rooftop PV. Load shapes do not significantly impact the values of the bill savings for all customer groups. Additionally, net metering causes a smaller variation in bill savings as compared to net billing, implying more flexibility for the customers to size their PV systems over a broader range. In contrast, net billing would encourage customers to limit their PV sizes, thereby mitigating the concerns of the utilities.
Created from Fastlane, Scopus look-up
Keywords: Bill savings; Net billing; Net metering; Rooftop PV; Thailand